Revision Pharyngoplasty in Cleft Palate and Velopharyngeal Insufficiency: Management and Outcomes. (May 2022) - Bruce, Madeleine K.; Zhang, Casey; Vodovotz, Lena; Irgebay, Zhazira; Maliha, Samantha; Pfaff, Miles; Ford, Matthew; Goldstein, Jesse A.; Losee, Joseph E.
Abstract : Introduction: Velopharyngeal insufficiency (VPI), a stigmatizing hallmark of palatal dysfunction, occurs in a wide spectrum of pediatric craniofacial conditions. The mainstays for surgical correction include palate repair and/or pharyngeal surgery. However, primary pharyngoplasty has a failure rate of 15% to 20%. Although revision pharyngoplasty may be necessary in those with persistent VPI, little is known regarding the indications for and outcomes after such procedures. The purpose of this study is to describe the authors' experience with indications for and outcomes after revision pharyngoplasty. Methods: A single-center retrospective review was performed of all patients undergoing revision pharyngoplasty between 2002 and 2019. Demographic data and Pittsburgh Weighted Speech Scores, diagnoses, comorbidities, and complications were tabulated. Two-tailed Student t test was used, and a P value of 0.05 or less was considered statistically significant. Results: Thirty-two patients (65.6% male) met inclusion criteria for this study. The most common diagnoses included cleft palate (68.8%), submucous cleft palate (SMCP, 18.8%), and congenital VPI (6.3%, likely occult SMCP). Most patients (84.4%) underwent palatoplasty before their initial pharyngoplasty. The primary indication for initial pharyngoplasty was VPI (mean age 7.1 ± 4.6 years). The most common indication for revision pharyngoplasty (mean age 11.2 ± 5.1 years) included persistent VPI (n = 22), followed by obstructive sleep apnea (OSA) (n = 11). Persistent VPI (n = 8) and OSA (n = 6) were the most common complications after secondary pharyngoplasty. Thirteen patients (40.6%) within the revision pharyngoplasty cohort required additional surgical intervention: 4 underwent tertiary pharyngoplasty, 4 underwent takedown for OSA (n = 3) or persistent VPI (n = 1), 3 underwent takedown and conversion Furlow for persistent VPI (n = 2), OSA (n = 2) and/or flap dehiscence (n = 1), and 2 underwent palatal lengthening with buccal myomucosal flaps for persistent VPI. Of the 4 patients who required a tertiary pharyngoplasty, the mean age at repair was 6.6 ± 1.1 years and their speech scores improved from 13.5 to 2.3 after tertiary pharyngoplasty ( P = 0.11). The overall speech score after completion of all procedures improved significantly from 19 to 3.3. Conclusion: Patients who fail primary pharyngoplasty represent a challenging population. Of patients who underwent secondary pharyngoplasty, nearly half required a tertiary procedure to achieve acceptable speech scores or resolve complications.